PEMAHAMAN KONTEKSTUAL TERHADAP NILAI KESAKSIAN WANITA DALAM AL-QUR’AN - Tasbih, Tasbih (AL-IRSYAD AL-NAFS: JURNAL BIMBINGAN DAN PENYULUHAN ISLAM, 2020)
The main issue to be answered in this paper is how is the contextual understanding of the value of women’s testimony in the Qur’an? This study is a literature review analyzed descriptively qualitatively, with theological and sociological approaches. The results show that based on a contextual understanding of the verses regarding women’s testimony, it can be said that the Qur’an never distinguishes between men and women. Al-Qur’an is precisely so respect and upholds the parallelism between men and women. However, if understood textually, it tends to show the opposite. Namely, women are still perceived as "second creatures" which then have implications for various kinds of injustice, for example in the case of testimony. As the implication that the Koran is not sufficiently understood textually so that it requires contextual understanding with complementary approaches.